A Terra Sigillata Itálica de Monte Molião, Lagos, Portugal - Arruda, Ana Margarida; Dias, Íris (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The extensive archaeological work carried out in Monte Molião since 2006 has shown a long diachrony of the site between the 4th century BC and the end of the 2nd century. The main building development that took place at the Flavian and Antonine times, concealed widely the previous constructions, namely the Julio-Claudian. Nevertheless, some archaeological data, such as italic terra sigillata, prove the permanence of human communities in Monte Molião that, since the Iron Age, lived there. The integrated study of this ceramic category, with the classification of ceramic fragments and respective shapes, it was taken into consideration the context of their collection, which enabled a better understanding of the consumption rhythms of the tableware in the beginning of the imperial phase, but also, to admit that the construction of some buildings may fall behind, at least, to the first half of the 1st century. The forms of the ceramic set correspond mainly to the Haltern Service I, despite the Service II being also present, which is not frequent in Algarve or in the rest of Portuguese territory, with the exception of Alcácer do Sal and somewhat Santarém as well.